Shikhara (superstructure) of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the garbhagriha (sanctum sanctorum) is made in the latina (vertical mono-spire) style. The bhadra (central offset) and pratibhadra (offset flanking bhadra) of the shikhara are profusely carved with chaitya (dormer windows) arches and the karna (corner offset) is decorated with chaitya arches and amalakas (crowning member of the latina shikhara shaped like a myrobalan fruit).